Binding selectivity of vitamin K3 based chemosensors towards nickel(II) and copper(II) metal ions - Patil, Amit; Lande, Dipali N.; Nalkar, Archana; (Gejji, Shridhar P.; Chakrovorty, Debamitra; Gonnade, Rajesh; Moniz, Tania; Rangel, Maria; Pereira, Eulalia; Salunke-Gawali, Sunita (Journal of molecular Structure, 2017)
The vitamin K3 derivatives 2-methyl-3-[(pyridin-2-ylmethyl)-amino]-1,4-naphthoquinone (M-1), 2-methyl-3-[(pyridin-2-ylethyl)-amino]-1,4-naphthoquinone (M-2), 2-methyl-3-((2-(thiophen-2-yl) methyl)amino)naphthalene-1,4-dione (M-3) and 2-methyl-3-((2-(thiophen-2-yl)ethyl)amino)naphthalene-1,4-dione (M-4) have been synthesized, characterized and studied for their chemosensor abilities towards transition metal ions. Crystal structures of M-1 to M-4 revealed a variety of N-H center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions. Minor variations in such interactions by chemical stimuli such as metal ions, results in change in color that can be visualized by naked eyes. It has been shown that electronic structure and H-1 NMR, vibrational as well as electronic spectra from the density functional theory agree well with the experiments. The metal ion binding in ethanol, ethanol-water and in mild base triethylamine brings forth recognizing ability of M-1 toward Ni2+ whereas M-2 exhibits large sensing ability for Cu2+ ion. Interestingly M-1 display varying metal ion binding specificity in different solvents with the association constant in ethanol being 11,786 M-1 for Ni2+ compared to 9462 M-1 for the Cu2+. A reversal in preferential binding of M-2 with the respective association constants being 4190 M-1 and 6370 M-1 is discernible. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone Molecular-structures; Anthraquinone; Aqueous-solution; Chemosensor; Crystal-structures; Cu(II); Derivatives; DFT; Fluorometric Chemosensors; hydrogen bonding; Naphthoquinone; pi-pi stacking; Recognition; sensors

Boron- and oxygen-doped π-extended helical nanographene with circularly polarised thermally activated delayed fluorescence - Venugopal, Geethu; Kumar, Viksit; Jadhav, Ashok Badrinarayan; Dongre, Sangram D.; Khan, Abujunaid; Gonnade, Rajesh; Kumar, Jatish; Santhosh Babu, Sukumaran (Chemistry-A European Journal, 2024)
Helical nanographenes have garnered substantial attention owing to their finely adjustable optical and semiconducting properties. The strategic integration of both helicity and heteroatoms into the nanographene structure, facilitated by a boron-oxygen-based multiple resonance (MR) thermally activated delayed fluorescence (TADF), elevates its photophysical and chiroptical features. This signifies the introduction of an elegant category of helical nanographene that combines optical (TADF) and chiroptical (CPL) features. In this direction, we report the synthesis, optical, and chiroptical properties of boron, oxygen-doped pi-extended helical nanographene. The pi-extension induces distortion in the DOBNA-incorporated nanographene, endowing a pair of helicenes, (P)-B2NG, and (M)-B2NG exhibiting circularly polarized luminescence with glum of -2.3x10-3 and +2.5x10-3, respectively. B2NG exhibited MR-TADF with a lifetime below 5 mu s, and a reasonably high fluorescence quantum yield (50 %). Our molecular design enriches the optical and chiroptical properties of nanographenes and opens up new opportunities in multidisciplinary fields. B, O-doped pi-extended helical nanographene has been explored for its optical and chiroptical properties. The presence of helical and nanographene segments stabilize the helicity and imparts tunable optical properties. Helical nanographene display circularly polarized thermally activated delayed fluorescence. image
Keywords: circularly polarized luminescence; DOBNA; dual emission; nanographene; TADF